Tabula: a web-based coordination tool integrating task structure overviews and minimalist task workspaces. (1st January 2013) - Kaptelinin, Victor; Björnfot, Patrik
The paper describes the design, implementation, and tentative evaluation of a web-based coordination tool named Tabula. The tool employs a shared representation that has the form of a task/participant table. Individual cells of the table are designed as minimalist interactive workspaces, each supporting a particular user in performing a particular task. Integrating overviews of the overall structure of participants' tasks with task management features within a single representation is intended to help the user identify pending tasks, facilitate access to task-related resources, and support an automatic update of projects' visual representations. A prototype of the tool has been evaluated within an informal web-based course. The results of the evaluation are discussed.